Evolusi Uang Dalam Perspektif Sejarah dan Al-Qur'an: Analisis Berdasarkan Pemikiran Wahbah Zuhaili - Doni Azhar; Elma Pujiana (Program Studi Perbankan Syariah Institut Al-Fithrah (IAF) Surabaya, 2023)
Money has evolved significantly from prehistoric times to modern times, serving as the foundation of the human economy and way of life. Historical, Qur'anic and Wahbah Zuhaili perspectives will be examined in this discussion. Evolution took us from a simple barter system to the creation of precious and distinctive coins such as gold and silver. An important role in the economy is played by cash. Money serves as an effective measure of value and medium of exchange, making it easy to compare the prices of various goods and services. Value can be stored and accumulated over time thanks to its wealth storage function. In addition, money serves as a mechanism of exchange that makes ordinary business easier. The role of gold, silver, dinars and dirhams as tools of trade and as units of value is recognized in the Qur'anic perspective. This idea was translated into the contemporary economic context by Wahbah Zuhaili. However, the emergence of paper money and cryptocurrencies prompted new questions about the function of money in the modern era. This research highlights the development and importance of money in human civilization by integrating history, religion and economics. We can understand how money has influenced and still shapes the economy and human existence as a whole by examining the ideas of value, exchange, and the social significance of money. From prehistoric times to the present, money has undergone significant transformations.